2016
DOI: 10.3847/0004-637x/821/1/6
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Astro-H Observations of Sloshing Gas Motions in the Cores of Galaxy Clusters

Abstract: Astro-H will be the first X-ray observatory to employ a high-resolution microcalorimeter, capable of measuring the shift and width of individual spectral lines to the precision necessary for estimating the velocity of the diffuse plasma in galaxy clusters. This new capability is expected to bring significant progress in understanding the dynamics, and therefore the physics, of the intracluster medium. However, because this plasma is optically thin, projection effects will be an important complicating factor in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 74 publications
2
19
0
Order By: Relevance
“…The first such mission will be Astro-H (Takahashi et al 2014), to be launched in early 2016. A recent study carried out by ZuHone et al (2016) used synthetic observations to show that Astro-H will be able to measure the basic kinematic properties of sloshing cold fronts, namely the shift of the spectral lines produced by the bulk motion of the sloshing gas (provided that our line of sight is at least partially within the sloshing plane) and the line broadening produced by the variation in this bulk motion and sloshing-driven turbulence. Unfortunately, they also showed that due to Astro-H's poor spatial resolution of ∼1', it will be unable to place any meaningful constraints on the ICM viscosity from studies of cold fronts.…”
Section: Future Observationsmentioning
confidence: 99%
“…The first such mission will be Astro-H (Takahashi et al 2014), to be launched in early 2016. A recent study carried out by ZuHone et al (2016) used synthetic observations to show that Astro-H will be able to measure the basic kinematic properties of sloshing cold fronts, namely the shift of the spectral lines produced by the bulk motion of the sloshing gas (provided that our line of sight is at least partially within the sloshing plane) and the line broadening produced by the variation in this bulk motion and sloshing-driven turbulence. Unfortunately, they also showed that due to Astro-H's poor spatial resolution of ∼1', it will be unable to place any meaningful constraints on the ICM viscosity from studies of cold fronts.…”
Section: Future Observationsmentioning
confidence: 99%
“…streaming motions. ZuHone et al (2016b), focusing on XRISM-like mock observations of bright central cluster regions in a relatively relaxed cluster with sloshing motions, also found that large number counts (10 3 or more) in the iron complex band are required to fully model the multi-component line shape. This is consistent with expectations obtained for observed systems in the preparatory studies for ASTRO-H (Kitayama et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Predictions for Astro-H (Hitomi) indicate in fact that higher number of photons, of order 10 3 -10 4 , are required to accurately model the iron complex shape with multiple velocity components (e.g. Shang & Oh 2012;ZuHone et al 2016b). In Table 2 (three rightmost columns) we therefore only report the best-fit results for the z1 mock spectrum, which are consistent with the numerical simulation estimates within the uncertainties.…”
Section: Xrism Resolve Mock Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subcluster is DM-only (perhaps stripped of its gas on a previous cluster passage). The initial conditions in the simulation explored here are the same as in previous works ([ [24][25][26][27][28] and Z21), and produce spiral-shaped cold fronts in an otherwise relatively relaxed cluster very similar to those observed in X-ray observations. In Z21, this simulation also produced thin strips of bubble material which closely resembled radio relics more than the "Merger2" simulation from that work.…”
Section: Merger Simulationsmentioning
confidence: 91%